Determinasi Pengetahuan Ibu dan Pengaruh Rokok terhadap Kejadian ISPA pada Balita: Karakteristik responden berdasarkan pengetahuan - Setiani, Eka Menik; Mirasa, Yudied Agung; Winarti, Eko (Sci-tech Journal, 2023)
ISPA disease occurs in toddlers because the child's immune system is still low. ISPA disease can be transmitted through saliva, sneezing, breathing air that contains germs that are inhaled by healthy people through their respiratory tract. Based on data from the Banjit health center, ARI is included in the 10 highest diseases in the working area of the Banjit health center, in 2022 ARI cases totaled 1184 cases. There were 371 cases in toddlers with ARI cases. The risk of smoking inside the house, residue can stick to curtains, sofas, roofs, even children's toys. Parents' smoking habit in the house makes toddlers passive smokers who are always exposed to cigarette smoke. The aim of the study was to determine (title) the factors associated with ARI in toddlers in the Banjit Health Center Work Area in 2022. using a quantitative cross-sectional method using the Simple Random Sampling technique. Data analysis looked for a relationship (title) using the chi square test, with independent variables and dependent variables (Knowledge, smoking habits, ARI under five). The study population was taken from 103 toddlers who were sick with ISPA from September to December 2022. With a sample of 84 toddlers. The results showed that there was a relationship between mother's knowledge (p-value = 0.002), smoking habits of family members (p-value = 0.004) and ARI in toddlers. The conclusion in this study is that there is a relationship between the determination of mother's knowledge and the effect of smoking on the incidence of ARI in toddlers. As an act of controlling ISPA in the working area of the Banjit Public Health Center, two risk factors are the top priority. Community support in creating a healthy living community movement (Germas) is especially sought not to smoke near toddlers.  Keywords: Knowledge, Smoking Habits, ARI under five